Determination of salmeterol, α‐hydroxysalmeterol and fluticasone propionate in human urine and plasma for doping control using UHPLC–QTOF–MS. (11th April 2021) - Sakellariou, Panagiotis; Petrou, Michael; Lyris, Emmanouil; Tsivou, Maria; Fragkaki, Argyro; Kiousi, Polyxeni; Angelis, Yiannis S.; Pistos, Constantinos
Abstract: Salmeterol and fluticasone are included in the Prohibited List annually issued by the World Anti‐Doping Agency. While for other permitted beta‐2 agonists a threshold has been established, above which any finding constitutes an Adverse Analytical Finding, this is not the case with salmeterol. The salmeterol metabolite, α ‐hydroxysalmeterol, has been described as a potentially more suitable biomarker for the misuse of inhaled salmeterol. In this study, a new and rapid UHPLC–QTOF–MS method was developed and validated for the simultaneous quantification of salmeterol, α ‐hydroxysalmeterol and fluticasone in human urine and plasma, which can be used for doping control. The analytes of interest were extracted by means of solid phase extraction and were separated on a Zorbax Eclipse Plus C18 column. Detection was performed in a quadrupole time‐of‐flight mass spectrometer equipped with an electrospray ionization source, in positive mode for the detection of salmeterol and its metabolite and in negative mode for the detection of fluticasone. Method was validated over a linear range from 0.10 to 2.00 ng/ml for salmeterol and fluticasone, and from 1.00 to 20.0 ng/ml for α ‐hydroxysalmeterol, in urine, whereas in plasma, the linear range was from 0.025 to 0.500 ng/ml for salmeterol and fluticasone, respectively.